2018
DOI: 10.1038/s41598-018-35780-y
|View full text |Cite
|
Sign up to set email alerts
|

Antrodia cinnamomea induces autophagic cell death via the CHOP/TRB3/Akt/mTOR pathway in colorectal cancer cells

Abstract: Antrodia cinnamomea, a well-known traditional medicine used in Taiwan, is a potent anticancer drug for colorectal cancer, but the upstream molecular mechanism of its anticancer effects remains unclear. In this study, A. cinnamomea extracts showed cytotoxicity in HCT116, HT29, SW480, Caco-2 and, Colo205 colorectal cancer cells. Whole-genome expression profiling of A. cinnamomea extracts in HCT116 cells was performed. A. cinnamomea extracts upregulated the expression of the endoplasmic reticulum stress marker CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…In HEC50 cells, phosphorylation of mTOR and AKT slightly decreased 1-6 h after PAM administration. This result is consistent with previous reports that suppression of mTOR pathway activates autophagy 28,29 . Interestingly, increased expression of LC3B protein was observed rapidly 0.5 hour after PAM treatment (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…In HEC50 cells, phosphorylation of mTOR and AKT slightly decreased 1-6 h after PAM administration. This result is consistent with previous reports that suppression of mTOR pathway activates autophagy 28,29 . Interestingly, increased expression of LC3B protein was observed rapidly 0.5 hour after PAM treatment (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Previous report found that induction of autophagy and apoptosis could prevent tumor growth in CRC cells 6. It has been found that phosphatidylinositol 3-kinase (PI3K)/Akt/mTOR signaling pathway is one of the major signaling pathways regulating autophagy and apoptosis in CRC 7,8. Apatinib, a small molecule tyrosine kinase inhibitor, demonstrated encouraging efficiency in human cancers 9,10.…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor which modulates cellular proliferation is autophagy. Recent reports indicated that AC induced autophagic cell death in colorectal cancer cells and triple-negative breast cancer (MDA-MB-231) cells [ 46 , 47 ]. Our results demonstrated that EEAC (50 μg/mL) induced autophagic marker LC 3II and p62 protein suggesting that autophagy also plays a central role in EEAC inhibition of T47D cells’ proliferation ( Figure 2 D).…”
Section: Discussionmentioning
confidence: 99%